A Review Article on Piles (Arsha) and its Management. - Swami, Sonu; Sharma, Vishnu Dutt (International Research Journal of Ayurveda & Yoga, 2023)
An important sub-discipline of Astanga Ayurveda, the Shalya tantra, is rich in many aspects of contemporary surgical thinking. As Arsha is one of the Anorectal disorders, Sushruta thoroughly discussed the achievements made by the Tantra in these conditions. The term "Arsha" is derived from "Ru Gatau" Dhatu and has the meaning of "as violent as an enemy" thanks to the suffix "Asun". It is the most prevalent anorectal condition and can strike anyone at any time. The aetiology, pathology, symptomatology, types, and management or therapy methods of Arsha are sufficiently detailed in Ayurveda. All the Ayurvedic classics include the causes of "Arsha" (Haemorrhoid), including the modern sedentary lifestyle, irregular eating habits, consumption of junk food, hot foods, non-fibrous meals, inactive occupations, mental stress, etc, are responsible for "Arsha" (Haemorrhoids), which results in impaired digestion, constipation, itchiness, searing pain, and soreness in the region of the Guda, all of which contribute to bleeding and the development of arsharoga. To prevent and treat Arsha while also avoiding its causes, acharyas critically outlined a variety of chikitsa modes (Nidanaparivarjana). Asthapana, Virechana, Asthapana and Anuvasana Basti for Vataja Arsha, Virechana for Pittaj Arsha, Aharadravya mixed with Sunthi and kulatha for Kaphaj Arsha, and Shamana Chikitsa for Raktaj Arsha, among others, are all applied based on the stages of Arsha and the Dosha involvement.